Application of Wireless Sensor Network in Target Detection and Localization - Hui Ding (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Wireless sensor network is a novel network with embedded system technology, communication technology and sensor technology as a whole, it is one of the wireless network form that is very rapid development at present, wireless sensor network has the characteristics of flexibility, adaptability, stable performance, wide coverage etc, so it is widely used in environmental monitoring, community security, military reconnaissance and other fields, the construction of target detection and location system in this paper are built by the application of wireless sensor network system platform, to realize the level of detection and localization of multiple targets. In this paper, wireless sensor network is first given a brief overview. On this basis, this paper also designs the target detection and location system, to presents a multi-objective hybrid location algorithm. Finally, the experiments verify that  DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3400